Gravity-driven microfluidic assay for digital enumeration of bacteria and for antibiotic susceptibility testing. Issue 1 (27th November 2019) - Kao, Yu-Ting; Kaminski, Tomasz S.; Postek, Witold; Guzowski, Jan; Makuch, Karol; Ruszczak, Artur; von Stetten, Felix; Zengerle, Roland; Garstecki, Piotr
Abstract : Easy-to-use gravity-driven step emulsification devices are capable of digital enumeration of bacteria and antibiotic susceptibility testing within 5 hours. Abstract : The alarming dynamics of antibiotic-resistant infections calls for the development of rapid and point-of-care (POC) antibiotic susceptibility testing (AST) methods. Here, we demonstrated the first completely stand-alone microfluidic system that allowed the execution of digital enumeration of bacteria and digital antibiograms without any specialized microfluidic instrumentation. A four-chamber gravity-driven step emulsification device generated ∼2000 monodisperse 2 nanoliter droplets with a coefficient of variation of 8.9% of volumes for 95% of droplets within less than 10 minutes. The manual workload required for droplet generation was limited to the sample preparation, the deposition into the sample inlet of the chip and subsequent orientation of the chip vertically without an additional pumping system. The use of shallow chambers imposing a 2D droplet arrangement provided superior stability of the droplets against coalescence and minimized the leakage of the reporter viability dye between adjacent droplets during long-term culture. By using resazurin as an indicator of the growth of bacteria, we were also able to reduce the assay time to ∼5 hours compared to 20 hours using the standard culture-based test.